On Domestication, Permanent and Temporary: Qoraŋә, Ǝlwelu, and Akwәqor - Vakhtin, Nikolai (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2021)
In this paper, I analyze a Yupik folklore plot represented by two stories. Both were recorded in 1940-41 by Ekaterina Rubtsova from two Ungazighmiit storytellers: Nalugyaq (1888–1942) and Tatko (ca. 1875–ca. 1944). The plot is as follows: A man abandons his older wife and two sons and leaves with his younger wife, taking away the herd and apparently leaving the old family to die. But they survive; the boys grow up, start to hunt, and finally come across a herd of wild deer grazing nearby. They tame the herd and fully domesticate it, then set on a journey in search of their father. Eventually they find their father, and once they reach their goal, the herd suddenly turns into a flock of cranes and flies away. Several questions require attention here: From the emic perspective, where is the line between tame and wild? What should a wild animal learn to do, or feel, or get accustomed to, or stop being afraid of, in order to become domestic? What are specific techniques of taming? What are the human-animal relations that enable people to tame the deer and at the same time leave an option for the deer to become wild again?